Rsk2, the Kinase Mutated in Coffin-Lowry Syndrome, Controls Cementum Formation. (July 2016) - Koehne, T.; Jeschke, A.; Petermann, F.; Seitz, S.; Neven, M.; Peters, S.; Luther, J.; Schweizer, M.; Schinke, T.; Kahl-Nieke, B.; Amling, M.; David, J.-P.
The ribosomal S6 kinase RSK2 is essential for osteoblast function, and inactivating mutations of RSK2 cause osteopenia in humans with Coffin-Lowry syndrome (CLS). Alveolar bone loss and premature tooth exfoliation are also consistently reported symptoms in CLS patients; however, the pathophysiologic mechanisms are unclear. Therefore, aiming to identify the functional relevance of Rsk2 for tooth development, we analyzed Rsk2-deficient mice. Here, we show that Rsk2 is a critical regulator of cementoblast function. Immunohistochemistry, histology, micro–computed tomography imaging, quantitative backscattered electron imaging, and in vitro assays revealed that Rsk2 is activated in cementoblasts and is necessary for proper acellular cementum formation. Cementum hypoplasia that is observed in Rsk2-deficient mice causes detachment and disorganization of the periodontal ligament and was associated with significant alveolar bone loss with age. Moreover, Rsk2-deficient mice display hypomineralization of cellular cementum with accumulation of nonmineralized cementoid. In agreement, treatment of the cementoblast cell line OCCM-30 with a Rsk inhibitor reduces formation of mineralization nodules and decreases the expression of cementum markers. Western blot analyses based on antibodies against Rsk1, Rsk2, and an activated form of the 2 kinases confirmed that Rsk2 is expressed and activated in differentiating OCCM-30 cells. To discriminate between periodontal bone loss and systemic bone loss, we additionally crossed Rsk2-deficient mice with transgenic mice overexpressing the osteoanabolic transcription factor Fra1. Fra1 overexpression clearly increases systemic bone volume in Rsk2-deficient mice but does not protect from alveolar bone loss. Our results indicate that cell autonomous cementum defects are causing early tooth loss in CLS patients. Moreover, we identify Rsk2 as a nonredundant regulator of cementum homeostasis, alveolar bone maintenance, and periodontal health, with all these features being independent of Rsk2 function in systemic bone formation.